Crianças e adolescentes nascidos de mães portadoras do HIV: um estudo sobre a relação mãe-filho no Vale Jequitinhonha - Thamara de Souza Campos (2011)
This study aimed to evaluate the mother-child relationship, among HIV-infected women living in Jequitinhonha Valley, Minas Gerais, Brazil. It is a cross sectional study consisting of a quantitative component, obtained through the Instrument "Quality of Family Interaction in view of the mother" and a qualitative component based on statements made by HIV positive mothers. Quantitative data were entered and analyzed using software Statistica 8.0 for Windows and qualitative data were transcribed and analyzed using content analysis proposed by Bardin. We interviewed a total of 30 mothers, 21 to 63 years, mean age 40.6 years (SD = 9.5), 36.5% (n = 11) are single, 53.3% (n = 13) studied 1 to 4 years, 43.3% (n = 13) live on less than a minimum wage and 40% (n = 12) represent the class D social strata. The number of children ranges from 1 to 9 children, with an average of 3.3 children (SD = 2.1), age of the youngest child is at least four and no more than 19 years, averaging 10, 5 years (SD = 4.3). The sexual route is the way of contamination in all cases, the average age of sexual debut is 19 years, and 70% (n = 21) began during adolescence, 53.3% (n = 16) had 1-3 sexual partners in her life.On pregnancy of the youngest child, 70% (n = 21) said it was not a planned pregnancy and that were tested for HIV in the last pregnancy, 93.3% (n = 28) had prenatal care, and an average of 5.9 visits (SD = 2.1). The quality of the mother and son, held by scores, reveals that 63.3% (n = 17) has a verbal and nonverbal very good with his son when it comes to talk all they said to talk with your teen while73.3% (n = 22) never to talk about HIV / AIDS. Participation of mothers in caring for the child, 73.3% (n = 22) has a good participation and 100% (n = 30) said they always take care of health of the child. Regarding the participation in school activities, cultural and leisure activities, 40% (n = 12) has a good participation in all activities and diseram mothers encourage their children to school take responsibility. Two categories emerged from interviews and content analysis:, the challenges and overruns, each with eight points of reflection of the relationship between mother and child in the context of HIV. We conclude from these results that there are qualitative and quantitative indicators of a good quality of mother-child relationship in all areas studied, in verbal and nonverbal communication, participation in care and participation in school activities, cultural and leisure activities. Despite the relationship between mother and son in the presence of HIV to be permeated by challenges, HIV-infected mothers struggle and overcome every day by their children.